2011
DOI: 10.1017/s1461145711001258
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in 5-hydroxytryptamine transporter expression causes adaptive changes in 5-HT4 receptor levels

Abstract: Genetic variation in 5-HT transporter (5-HTT) expression is a key risk factor for psychiatric disorder and has been linked to changes in the expression of certain 5-HT receptor subtypes. This study investigated the effect of variation in 5-HTT expression on 5-HT 4 receptor levels in both 5-HTT knockout (KO) and overexpressing (OE) mice using autoradiography with the selective 5-HT 4 receptor radioligand,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Specifically, we observed this effect within the neocortex and a trend for a similar effect within the caudate whereas we did not observe evidence for an effect of 5-HTTLPR status on [ 11 C]SB207145 binding within subcortical regions including the amygdala, hippocampus and putamen. Previous studies in animal models have reported that 5-HT 4 levels show a monotonic response to chronic changes in 5-HT levels (Jennings et al, 2011;Licht et al, 2010;Vidal et al, 2009). Based on these animal studies, our current findings suggest that 5-HTTLPR status may contribute to differences in cerebral 5-HT levels that are identifiable in humans using in vivo neuroimaging.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, we observed this effect within the neocortex and a trend for a similar effect within the caudate whereas we did not observe evidence for an effect of 5-HTTLPR status on [ 11 C]SB207145 binding within subcortical regions including the amygdala, hippocampus and putamen. Previous studies in animal models have reported that 5-HT 4 levels show a monotonic response to chronic changes in 5-HT levels (Jennings et al, 2011;Licht et al, 2010;Vidal et al, 2009). Based on these animal studies, our current findings suggest that 5-HTTLPR status may contribute to differences in cerebral 5-HT levels that are identifiable in humans using in vivo neuroimaging.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study in mice reported that homozygous knock-out of the gene coding for the 5-HTT resulted in a down-regulation of 5-HT 4 binding measured with [ 3 H]SB207145 (Jennings et al, 2011). Conversely, over-expression of the gene coding for the 5-HTT resulted in increased 5-HT 4 binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out adaptive changes in the serotoninergic system, including variations in 5-HT 4 receptor levels, which could explain the absence of behavioral effects of fluoxetine in 5-HT 1A receptor KO mice. Indeed, decreases in the density of the serotonin transporter (5-HTT) were measured in several brain regions of these 5-HT 1A mutant mice (Ase et al, 2001), and a recent study described that variation in serotonin transporter expression could cause adaptive changes in 5-HT 4 receptor levels in serotonin transporter overexpressing mice (Jennings et al, 2012).…”
Section: Requirement Of 5-ht 4 Receptors For the Behavioral And Neuromentioning
confidence: 99%
“…SERT knockout rats exhibit highly parallel findings to those found in SERT knockout mice. Transgenic SERT over-expressing mice show reduced anxiety and related behaviors and other reversed phenomena including serotonin receptor changes compared to SERT-deficient mice (reviews: [41, 55]).…”
Section: Introductionmentioning
confidence: 99%